Investigation of the effects of different nanoparticle additionals on the mechanical properties of silicone elastomer used in maxillofacial prosthesis - Karaman, Gamze; Altıntaş, Eyyüp (MediHealth Academy Yayıncılık, 2022)
Objective: The aim of this study is to evaluate the change in the mechanical properties of silicone elastomer used in the production of maxillofacial prostheses with the addition of 3 different nanoparticles (TiO2-SiO2-ZnO). Material and Method: TiO2-SiO2-ZnO nanoparticles were added to the A part of the M511 Platinum (Technovent Ltd., England) silicone elastomer at a rate of 2% by weight. Test specimens were produced in sizes by ASTM D412 standards for tensile strength and percent elongation, ASTM D624 for tear strength, and ASTM D2240-68 for hardness testing. For each mechanical test, 4 groups were formed together with the control group and 3 other groups to which nanoparticles were added, and a total of 132 samples were produced, 11 samples for each group (n=11), (N=132). The data of tensile strength, elongation percentage, and tear strength tests were analyzed by Shapiro Wilk's and/or Kolmogorov Smirnov/Mann Whitney U, Kruskal Wallis-H tests; for the hardness test, the values ??in each group showed a normal distribution within themselves, hardness test was analyzed with Oneway ANOVA/Tukey HSD tests. Results: The addition of TiO2 and SiO2 to the silicone elastomer significantly increased the tensile strength compared to the other groups (p
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi